A type II secreted subtilase from commensal rhizobacteria cleaves immune elicitor peptides and suppresses flg22-induced immune activation - Samuel Eastman; Ting Jiang; Kaeli Ficco; Chao Liao; Britley Jones; Sarina Wen; Yvette Olivas Biddle; Aya Eyceoz; Ilya Yatsishin; Todd A. Naumann; Jonathan M. Conway (Cell Reports)
Summary: Plant roots grow in association with a community of microorganisms collectively known as the rhizosphere microbiome. Immune activation in response to elicitors like the flagellin-derived epitope flg22 restricts bacteria on plant roots but also inhibits plant growth. Some commensal root-associated bacteria are capable of suppressing the plant immune response to elicitors. In this study, we investigated the ability of 165 root-associated bacteria to suppress flg22-induced immune activation and growth restriction. We demonstrate that a type II secreted subtilase, which we term immunosuppressive subtilase A (IssA), from Dyella japonica strain MF79 cleaves the immune elicitor peptide flg22 and suppresses immune activation. IssA homologs are found in other plant-associated commensals, with particularly high conservation in the order Xanthomonadales. This represents a novel mechanism by which commensal microbes modulate flg22-induced immunity in the rhizosphere microbiome.